Commercial Aviation Safety, Sixth Edition - Cusick, Stephen K.; Cortes, Antonio I.; Rodrigues, Clarence C. (McGraw-Hill Education, 2017)
Completely revised to fully align with current U.S. and international regulations, this hands-on resource clearly explains the principles and practices of commercial aviation safety--from accident investigations to Safety Management Systems. Commercial Aviation Safety, Sixth Edition, delivers authoritative information on today's risk management on the ground and in the air. The book offers the latest procedures, flight technologies, and accident statistics. You will learn about new and evolving challenges, such as lasers, drones (unmanned aerial vehicles), cyberattacks, aircraft icing, and software bugs. Chapter outlines, review questions, and real-world incident examples are featured throughout.